The population history of the Chinese in the Philippines an evaluative historiography - Alejandro, Clark L. (2010)
This essay evaluates recent scholarship on the history of the Chinese in the Philippines through a discussion of our current knowledge of Chinese population and migration data during the colonial period. It identifies new sources and argues for the importance of certain frameworks in the study of Chinese population history in the Philippines. It recommends the use of a stronger transnational framework with a sensitivity to anthropological concerns, such as the formation of a Chinese family identity, and finding the translocal within the transnational community.
Keywords: Demography; Chinese populations in the Philippine